Sistem Informasi Pengendalian Stok Bahan Baku Pada CV. Bulu Nusantara Gresik - Agung Setyo Fanani; Emmy Wahyuningtyas (Informatics Engineering Department-UWKS, 2017)
Control of raw material inventory that still manual can hamper the production target, because it does not close the possibility of a mistake in the calculation of raw materials that result in lack of raw materials inventory and production will stop. During this stock control of raw materials produced in CV. Bulu Nusantara Gresik done by the production section manually by using standardization of determination which has been determined by the leadership of the company. By determining the supply of raw materials manual has many shortcomings, among others, if there is a mistake in the prediction could be CV. Fur Nusantara Gresik the excess stock (over stock) or low stock (out of stock). This research produces information system of stock control of raw material for smoothness of production process at CV. Bulu Nusantara Gresik to get raw material information obtained more quickly and accurately.